The Phenomenon Of Free Sex And Sexually Transmitted Infections Among Teenagers - Amira Manzilatul Latifah; Meilia Rahmawati Kusumaningsih (Universitas Prima Indonesia, 2026)
This study addresses the phenomenon of risky sexual behavior and sexually transmitted infections (STIs) among adolescents, which is a serious public health problem. Adolescents aged 15-24 years have a high risk of STIs due to unsafe sexual behavior, which is triggered by a lack of sex education and the influence of the social environment. This study used the literature review method to analyze various relevant sources regarding risky sexual behavior and its impact. The results show that risky sex among adolescents has the potential to cause various health problems, including STIs and unwanted pregnancies. Factors influencing this behavior include peer pressure, media influence, and inadequate parental control, which exacerbate the situation. In addition, education on reproductive health is essential to address this issue, as it not only provides knowledge about reproductive organs but also increases awareness of the dangers associated with risky sexual behavior and STIs. Therefore, comprehensive reproductive health education is needed to increase adolescents' awareness of the risks associated with risky sexual behavior and STIs.